What Acute Stress Protocols Can Tell Us About PTSD and Stress-Related Neuropsychiatric Disorders - Musazzi, Laura; Tornese, Paolo; Sala, Nathalie; Popoli, Maurizio (Frontiers in Pharmacology, 2018)
Posttraumatic Stress Disorder (PTSD), the fifth most prevalent mental disorder in the US, is a chronic, debilitating mental illness with as yet limited options for treatment. Hallmark symptoms of PTSD include intrusive memory of trauma, avoidance of reminders of the event, hyperarousal and hypervigilance, emotional numbing and anhedonia. PTSD is often triggered by exposure to a single traumatic experience, such as a traffic accident, a natural catastrophe, or an episode of violence. This suggests that stressful events have a primary role in the pathogenesis of the disorder, although genetic background and previous life events are likely involved. However, pathophysiology of this mental disorder, as for major depression and anxiety disorders, is still poorly understood. In particular, it is unknown how can a single traumatic, stressful event induce a disease that can last for years or decades. A major shift in the conceptual framework investigating neuropsychiatric disorders has occurred in recent years, from a monoamine-oriented hypothesis (which dominated pharmacological research for over half a century) to a neuroplasticity hypothesis, which posits that structural and functional changes in brain circuitry (largely in the glutamate system) mediate psychopathology and also therapeutic action. Rodent stress models are very useful to understand pathophysiology of PTSD. Recent studies with acute or subacute stress models have shown that exposure to short-time stressors (from several minutes to a few hours) can induce not only rapid, but also sustained changes in synaptic function (glutamate release, synaptic transmission/plasticity), neuroarchitecture (dendritic morphology, synaptic spines) and behavior (cognitive functions). Some of these changes, e.g., stress-induced increased glutamate release and dendrite retraction, are likely connected and occur more rapidly than previously thought. We propose here to use a modified version of a simple and validated protocol of footshock stress to explore different trajectories in the individual response to acute stress. This new conceptual framework may enable us to identify determinants of resilient versus vulnerable response as well as new targets for treatment, in particular for rapid-acting antidepressants. It will be interesting to investigate the putative prophylactic action of ketamine towards the maladaptive effects of acute stress in this new protocol.